2015
DOI: 10.1093/europace/euv234
|View full text |Cite
|
Sign up to set email alerts
|

Personalized and automated remote monitoring of atrial fibrillation

Abstract: This work demonstrates the ability of a pilot system to classify alerts and improves personalized remote monitoring of patients. In particular, our method allows integration of patient medical history with device alert notifications, which is useful both from medical and resource-management perspectives. The system was able to automatically classify the importance of 1783 AF alerts in 60 patients, which resulted in an 84% reduction in notification workload, while preserving patient safety.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 12 publications
0
17
0
1
Order By: Relevance
“…Ours is not the first study to utilize unstructured EHR data in AF research. [1517,23] Our study builds on this previous work through the use of text data with an NLP pipeline, the calculation of additional risk scores and an analysis of prescribing patterns. Whilst we evaluate our pipeline in the context of AF, our aim is to provide an open tool for clinical risk scoring calculations in general.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ours is not the first study to utilize unstructured EHR data in AF research. [1517,23] Our study builds on this previous work through the use of text data with an NLP pipeline, the calculation of additional risk scores and an analysis of prescribing patterns. Whilst we evaluate our pipeline in the context of AF, our aim is to provide an open tool for clinical risk scoring calculations in general.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have found it is possible to accurately predict CHA 2 DS 2 -VASc using EHR text. [1517] We build on this work to develop a flexible open source pipeline and calculate additional risk scores. Our specific objectives are to:…”
Section: Introductionmentioning
confidence: 99%
“…• Identify at-risk patients early (even before symptoms develop) and permit pre-emptive care (Boehmer 2017, Rosier et al, 2016).…”
Section: Healthcare Deliverymentioning
confidence: 99%
“…ML applications have allowed for risk stratification, improved arrhythmia localisation and streamlined remote monitoring which may significantly reduce the workload faced by electrophysiologists. [ 42 44 ]…”
Section: Cardiac Implantable Electronic Devicesmentioning
confidence: 99%
“…Rosier et al examined the potential for ML to automate monitoring of alerts from CIEDs. [ 44 ] They used natural language processing to examine EHR data to determine the significance of AF alerts from CIEDs. The natural language processing algorithm was able to calculate CHA 2 DS 2 -VASc scores and anticoagulant status for each patient and thus, classify the importance of the AF alert.…”
Section: Cardiac Implantable Electronic Devicesmentioning
confidence: 99%